2011
DOI: 10.1038/ki.2011.42
|View full text |Cite
|
Sign up to set email alerts
|

The severity of acute kidney injury predicts progression to chronic kidney disease

Abstract: Acute kidney injury (AKI) is associated with progression to advanced chronic kidney disease (CKD). We tested whether patients who survive AKI and are at higher risk for CKD progression can be identified during their hospital admission, thus providing opportunities to intervene. This was assessed in patients in the Department of Veterans Affairs Healthcare System hospitalized with a primary diagnosis indicating AKI (ICD9 codes 584.xx). In the exploratory phase, three multivariate prediction models for progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
456
2
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 638 publications
(492 citation statements)
references
References 24 publications
19
456
2
5
Order By: Relevance
“…We also clarified that the severity and frequency of proximal tubule injury underlies the degree of AKI to CKD progression. [9][10][11][12] The reversibility of fibrosis after the regeneration of proximal tubules was shown with mild proximal tubule injury, and the presence of proximal-distal tubule crosstalk was confirmed. Our data strongly support the importance of protecting proximal tubules to halt AKI to CKD progression.…”
mentioning
confidence: 84%
“…We also clarified that the severity and frequency of proximal tubule injury underlies the degree of AKI to CKD progression. [9][10][11][12] The reversibility of fibrosis after the regeneration of proximal tubules was shown with mild proximal tubule injury, and the presence of proximal-distal tubule crosstalk was confirmed. Our data strongly support the importance of protecting proximal tubules to halt AKI to CKD progression.…”
mentioning
confidence: 84%
“…5). For example, patients who have more severe or persistent AKD 11,96 , those with premorbid conditions that increase the risk of future CKD progression (for example, those with evidence of pre-existing CKD, diabetes and/or proteinuria), and those with recurrent disease or non-recovery (for example, those with congestive heart failure, cirrhosis, and/or malignancy with or without chemotherapy) might achieve greater benefit from earlier or more frequent surveillance than patients with a lower risk of future CKD 97,98 . This hypothesis is supported by data showing that rates of re-hospitalization and recurrent AKI are high among patients with similar risk factors 95,[98][99][100][101][102][103][104] .…”
Section: Follow-up Carementioning
confidence: 99%
“…In addition, several adult studies have demonstrated a dose-response relationship between AKI and CKD, including a higher risk of CKD in those with more severe AKI and also in those with repeated episodes of AKI [35][36][37]. Several pediatric observational studies have also shown a high proportion of CKD in survivors of AKI, ranging from 10 to 69%, but these studies have focused on populations without primary kidney disease [38][39][40][41][42][43][44].…”
Section: Aki and Ckd Associationmentioning
confidence: 99%